2016
DOI: 10.1093/neuonc/now148
|View full text |Cite
|
Sign up to set email alerts
|

MR perfusion-weighted imaging in the evaluation of high-grade gliomas after treatment: a systematic review and meta-analysis

Abstract: Background. Distinction between tumor and treatment related changes is crucial for clinical management of patients with high-grade gliomas. Our purpose was to evaluate whether dynamic susceptibility contrast-enhanced (DSC) and dynamic contrast enhanced (DCE) perfusion-weighted imaging (PWI) metrics can effectively differentiate between recurrent tumor and posttreatment changes within the enhancing signal abnormality on conventional MRI. Methods. A comprehensive literature search was performed for studies evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
177
1
2

Year Published

2018
2018
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 202 publications
(193 citation statements)
references
References 47 publications
(120 reference statements)
4
177
1
2
Order By: Relevance
“…) than treatment effects (Fig. ) . rCBV is high in tumor, as it is reflective of the tumor hyperperfusion volume.…”
Section: Pseudoprogressionmentioning
confidence: 92%
“…) than treatment effects (Fig. ) . rCBV is high in tumor, as it is reflective of the tumor hyperperfusion volume.…”
Section: Pseudoprogressionmentioning
confidence: 92%
“…However, in a large meta-analysis of data from 28 articles published since 2005, the pooled sensitivity and specificity of DSC was 90% and 88%, respectively, for detecting true tumor recurrence in the setting of possible pseudoprogression. 37 Thus the totality of the evidence indicates that DSCis fairly accurate in identifying true tumor progression. Achieving even greater accuracy may require combining DSC data with other advanced imaging modalities such as DTI, 38 ASL, 39 and MRS. 40, 41 This is not guaranteed, however; a recent meta-analysis of 9 studies found that monoparametric and multiparametric MRI performed equally in a clinical context.…”
Section: Clinical Applications Of Advanced Mrimentioning
confidence: 99%
“…CURRENTLY, high‐grade glioma (HGG) treatment consists of combination of surgery, radiation, and chemotherapy (ie, temozolomide). This triple therapy commonly leads to treatment‐related imaging changes in the form of contrast enhancing lesions that closely mimic glioma recurrence on conventional magnetic resonance imaging (MRI) . This imaging dilemma is not uncommon; a recent meta‐analysis revealed that 36% of patients with enhancing lesion on posttreatment MR have treatment‐related changes, while true progression occurred only in 60% of patients .…”
mentioning
confidence: 99%
“…This imaging dilemma is not uncommon; a recent meta‐analysis revealed that 36% of patients with enhancing lesion on posttreatment MR have treatment‐related changes, while true progression occurred only in 60% of patients . Compared with conventional MRI, MR perfusion techniques provide information about physiologic parameters of these lesions through its ability to indirectly evaluate tumor neovascularity …”
mentioning
confidence: 99%
See 1 more Smart Citation